1992
DOI: 10.1002/ar.1092340206
|View full text |Cite
|
Sign up to set email alerts
|

Localization and activity of Na+, K+ ‐ATPase in the ductuli efferentes of the rat

Abstract: The Na+,K(+)-ATPase enzyme through its p-nitrophenyl phosphatase activity was localized in the ductuli efferentes of rats. Enzymatic activity was demonstrated along the cytoplasmic side of the plasmalemma of the ductular epithelial cells. The most intense deposition of reaction products was found on the plasmalemma delimiting the lower lateral and basal regions of the cells. The plasma membranes forming the microvilli, apical junctional complexes were devoid of reaction product while the midlateral membranes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 51 publications
2
45
1
Order By: Relevance
“…In this group, cell height was still significantly reduced in comparison to control levels at day 35; although a small decrease was still evident in adulthood, this did not reach statistical significance. The reduction in epithelial cell height was not as severe after the administration of lower doses of DES (1 and 0.1 pg); by either day 75 (DES 1 pg) or day 35 (DES 0.1 pg), epithelial cell heights had recovered to control levels. Administration of ethinyl estradiol induced a reduction in epithelial cell height which was similar in magnitude to that induced by 10 pg DES at all ages assessed (Fig.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…In this group, cell height was still significantly reduced in comparison to control levels at day 35; although a small decrease was still evident in adulthood, this did not reach statistical significance. The reduction in epithelial cell height was not as severe after the administration of lower doses of DES (1 and 0.1 pg); by either day 75 (DES 1 pg) or day 35 (DES 0.1 pg), epithelial cell heights had recovered to control levels. Administration of ethinyl estradiol induced a reduction in epithelial cell height which was similar in magnitude to that induced by 10 pg DES at all ages assessed (Fig.…”
Section: Resultscontrasting
confidence: 65%
“…The greatest effects always occurred after the administration of 10 pg DES, and lesser effects were observed after the administration of the two lower doses (1 and 0.1 pg), although the differences between these two lower doses were sometimes marginal. At time points beyond day 25, dose-dependent effects of DES were still evident on testis weights, and epithelial cell height of the efferent ducts still exhibited dose-dependent changes at days 35 estradiol regarded the more severe distension and overgrowth of the rete testis in the DEStreated cohorts. The overgrowth of the rete testis induced by these potent estrogens may be related to the increased incidence of rete testis adenocarcinoma (normally a rare neoplasm) that has been observed in both humans and mice exposed to DES in utero (30,31).…”
Section: Discussionmentioning
confidence: 95%
“…The presence of high levels of Na¤-K¤-ATPase activity in the basolateral membranes of the rat efferent ducts has been well documented (Byers & Graham, 1990;Ilio & Hess, 1992) suggesting that fluid transport via the Na¤-H¤ exchanger is coupled to the sodium pump. Unpublished data from this laboratory (L. A. Hansen, J. Clulow & R. C. Jones) indicates a parallel requirement for Cl¦ during Na¤ and fluid reabsorption, suggesting that, as in the proximal tubule (Baum, 1987;Preisig & Rector, 1988) a Cl¦-base antiporter may operate in parallel with the Na¤-H¤ exchanger, resulting in net electroneutral transcellular reabsorption of NaCl.…”
Section: ------------------------------------------------------------mentioning
confidence: 98%
“…The correlation between Na¤ and fluid reabsorption suggests that fluid reabsorption in the efferent ducts is dependent upon the transport of Na¤ across the epithelium, as has been demonstrated for the proximal kidney tubules which are homologous to the efferent ducts (Giebisch et al 1964;Berry & Rector, 1991). Although Na¤-K¤-ATPase activity in the efferent ducts (Byers & Graham, 1990;Ilio & Hess, 1992 may contribute substantially to the removal of sodium from the basal side of the epithelium, little is known of transporters which may mediate luminal entry. In the proximal kidney tubules, the role of a Na¤-H¤ antiporter in epithelial transport is well documented in both vesicle and intact tubule preparations (Baum, 1987;Preisig & Rector, 1988;Berry & Rector, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using electron dense tracers confirmed that these organelles are involved in endocytosis (Hermo and Morales, 1984;Veeramachaneni and Amann, 1991;. Second, it is proposed that electrolytes and consequently water are reabsorbed across the epithelium by means of membrane-associated transporters and channels (Ilio and Hess, 1992;Clulow et al, 1998;Fisher et al, 1998). Third, it is possible that small molecules can move paracellularly between the adjoining cells because the barrier of the efferent ductule epithelium is assumed to be leaky (Suzuki and Nagano, 1978).…”
mentioning
confidence: 99%